Macronutrient fertilizers on basil growth and yield - Lima, Janderson Carmo; Nascimenro, Marilza Neves; Oliveira, Uasley Caldas; Santos, Anacleto Ranulfo; Silva, Alinsmario Leite (Comunicata Scientiae, 2020)
The objective of this work was to determine the macronutrient doses that allow the highest phytomass yield and growth of basil plants. The experiment was carried out in the experimental area of ​​the Federal University of Recôncavo da Bahia, in Cruz das Almas, BA, in a greenhouse. The treatments were obtained according to the Baconian matrix statistical arrangement, in which one of the nutrients is supplied in variable amounts, while the others are kept at a referential level. Six nutrients (nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg) and sulfur (S)) were evaluated in three different doses, and two additional treatments, one with reference doses and another without nutrient addition, totaling 20 treatments that were arranged in a completely randomized design with five replications, totaling 100 experimental units. At 50 days after treatment distribution, the growth parameters were evaluated: Plant height, number of leaves, leaf dry mass, stem, root and leaf area. It was observed that the highest leaf dry mass accumulation was estimated with the dose of 250 mg dm³ of N giving an average of 8.01g per plant, being significantly higher when compared to all other tested elements, this parameter is extremely relevant because the leaves are characterized as the main product of this species. Phosphorus doses allowed significant results in height and leaf area, whereas K favored higher leaf emission. Positive responses were verified for nutrients Ca, Mg and S in all parameters tested at levels above those tested as reference.